High resolution hematite/goethite records from Chinese loess sequences for the last glacial-interglacial cycle: Rapid climatic response of the East Asian Monsoon to the tropical Pacific - Ji, JF; Chen, J; Balsam, W; Lu, HY; Sun, YB; Xu, HF (Geophysical Research Letters, 2004)
In order to study the variability of dry versus humid conditions resulting from the East Asian monsoon (EAM) we analyzed hematite and goethite from two high-resolution Chinese loess sections by diffuse reflectance spectroscopy. The hematite and goethite concentrations are higher in interglacial paleosols than in glacial loess sediments, whereas the hematite/goethite (Hm/Gt) ratios are lower in paleosols than in loess. Such changes are consistent with higher precipitation and temperature and increased pedogenesis during interglaciation and lower precipitation and temperature and decreased pedogenesis during glaciation. The Hm/Gt ratio can be employed as a tool to assess short-term variations in humidity and aridity of the EAM. The Hm/Gt ratios of the last glacial loess displays millennial-scale abrupt climate oscillations, revealing a pattern of significantly reduced and enhanced summer monsoon moisture. Our results indicate that the EAM responded to tropical Pacific climate by millennial-scale changes in precipitation during the last glaciation.